Impact of GST on small business sector in Haryana - Dr Ritu; Monika (Innovative Research Thoughts, 2017)
Haryana's small businesses have been greatly affected by India's GST. This abstract explores GST's effects on small enterprises' potential and problems. Small Haryana firms have benefited from GST. It consolidated indirect taxes under a single tax structure. This streamlining has made tax compliance simpler for small firms. Small enterprises have become more competitive by eliminating cascading effects using the input tax credit system. Small enterprises may now reach clients beyond their state and compete, which has improved product quality and efficiency. Haryana's small enterprises also face GST issues. Understanding the new tax structure, changing accounting systems, and using the GST site were initially challenging. These issues created company interruptions and demanded compliance efforts. Small firms spend more time and money on compliance needs like filing taxes and keeping records. GST has had both pros and cons for Haryana's small businesses. While tax simplification and streamlining have lowered compliance load and boosted competitiveness, small firms have faced early transition issues and increased compliance obligations. Understanding these distinctions may assist policymakers, business groups, and entrepreneurs develop strategies to optimise GST advantages and manage small company issues in Haryana.